2019
DOI: 10.3390/jcm8070915
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Skeletal Muscle Kynurenine Metabolism in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background: Loss of peripheral muscle oxidative phenotype, cognitive impairment, and depression are well-recognized systemic manifestations of chronic obstructive pulmonary disease (COPD). Kynurenine (KYN), known to be associated with disturbed mental health, can be metabolized in muscle by kynurenine aminotransferases (KAT) 1–4. These KATs are regulated by peroxisome proliferator-activated receptor gamma (PPARγ) coactivator-1α (PGC1α). We hypothesize that impaired PGC1α signaling in COPD is associated with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…Smoking showed a strong influence on the natural history of chronic obstructive pulmonary disease (COPD) and smoking related COPD was a significant predictor of more visit to emergency room and hospital readmission in colon cancer patients treated with adjuvant chemotherapy [39,40]. Experimental evidences revealed that smoking could influence skeletal muscle depletion and some muscle metabolism might be impaired in COPD patients [41,42]. Based on these effects of smoking, we believe that the trajectory association among smoking, body composition changes, and chemotherapy tolerance in patients with colon cancer needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking showed a strong influence on the natural history of chronic obstructive pulmonary disease (COPD) and smoking related COPD was a significant predictor of more visit to emergency room and hospital readmission in colon cancer patients treated with adjuvant chemotherapy [39,40]. Experimental evidences revealed that smoking could influence skeletal muscle depletion and some muscle metabolism might be impaired in COPD patients [41,42]. Based on these effects of smoking, we believe that the trajectory association among smoking, body composition changes, and chemotherapy tolerance in patients with colon cancer needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In muscle, kynurenine can also be metabolised and cleared by kynurenine aminotransferases that are regulated by PGC-1α. Interestingly, a recent study of our group showed reduced expression levels of these aminotransferases in skeletal muscle of patients with COPD, which might explain the elevated plasma kynurenine levels 27. Impairments in the kynurenine pathway have been linked to anxiety, depression and cognitive decline 28…”
Section: Introductionmentioning
confidence: 97%
“…The extrapulmonary manifestations in COPD are linked by the cross-talk between the gut–muscle–brain axis which includes the vagus nerve, gut hormone signalling, the immune system, serotonin and tryptophan metabolism and microbial metabolites such as short-chain fatty acids 25. All routes might be disturbed in patients with COPD, but especially serotonin and tryptophan metabolism has recently been shown to be impaired in patients with COPD leading to unfavourable higher kynurenine/tryptophan ratios in the circulation 26 27. By modulating tryptophan availability, the microbiota can regulate the kynurenine pathway decreasing plasma kynurenine levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed functional and regulatory aspects of the KYN pathway have been reviewed elsewhere. 1 The KYN pathway is deregulated in various chronic diseases, such as different internal (eg, chronic obstructive pulmonary disease, 4 diabetes, 2 cancer 5 ) or neurological (eg, multiple sclerosis, 6 Alzheimer and Parkinson disease 7 ) disorders. When compared with healthy controls, most of these diseases show a persistent overactivation of the KYN pathway as indicated by elevated levels of KYN and the KYN/TRP ratio.…”
Section: Introductionmentioning
confidence: 99%